A case of pneumoperitoneum after diagnostic colonoscopy for ulcerative colitis managed conservatively: a rare but possible complication - Patel, Neel B.; Desai, Hitendra K.; Doshi, Purvesh; Javia, Bansil (International Surgery Journal, 2021)
Ulcerative colitis is a chronic disease characterized by recurring episodes of inflammation of the colonic mucosae. Patients with ulcerative colitis are at an increased risk of perforations due to friability of colonic mucosa. Colonoscopy is usually regarded as a safe procedure, but complications may occur. Perforations associated with colonoscopy are dreaded complications. Most patients with pneumoperitoneum require surgical intervention, with associated major postoperative morbidity and mortality. This case report describes a 30 year old female presenting with an extensive pneumoperitoneum 2 days after colonoscopy done for her complaint of melena for one week. Colonoscopy was suggestive of severe active colitis in background of chronic ulcerative colitis. Histopathological reports s/o inflammatory bowel disease ulcerative colitis likely. CT Abdomen was s/o diffuse concentric thickening of the large bowel more predominantly seen in rectosigmoid colon, ascending colon, caecum, IC junction and consistent with inflammatory bowel disease and moderate pneumoperitoneum noted. The patient remained stable despite intraperitoneal free air. Patient was managed conservatively and no surgical intervention needed.